Digital currency and payment innovation in the hospitality and tourism industry - Kim, Jinkyung Jenny; Radic, Aleksandar; Chua, Bee-Lia; Koo, Bonhak; Han, Heesup (Elsevier, 2022)
This paper examined the acceptance of central bank digital currency (CBDC) as a payment method in the hospitality and tourism sectors. The characteristics of CBDC payment were discussed and the five-stage consumer adoption model served as a framework for advancing our knowledge about individuals’ adoption process of payment innovation. In addition, this study involved consumer innovativeness as a moderating factor in the formation of consumer adoption behavior. Based on 423 responses collected from self-administrated online survey, we conducted the structural equation modeling analysis and metric invariance test. The proposed model, which incorporates innovation characteristics and the consumer adoption process, properly predicted consumer acceptance toward CBDC payment in buying hospitality and tourism products. Furthermore, the identified moderating role of consumer innovativeness in the relationships, such as one between interest and evaluation, and the other between evaluation and trial intention promoted a better understanding of the consumer adoption behavior toward payment innovation.